Perlindungan Hukum Terhadap Korban Tindak Pidana Kekerasan Dalam Rumah Tanggan (KDRT) Di Kota Binjai - Aulia, Sindi; Ismaidar, Ismaidar (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze legal protection for victims of domestic violence (KDRT) in Binjai City based on Law Number 23 of 2004 concerning the Elimination of Domestic Violence. This study is based on the increasing cases of domestic violence in Indonesia, which indicates that there are still obstacles in the implementation of Law Number 23 of 2004. The focus of the study includes law enforcement related to domestic violence and the obstacles faced in it. This study uses a descriptive method with a normative legal approach, which refers to the analysis of regulations, legal theory, and other supporting documents. Secondary data were obtained from literature such as books, journals, and previous research results. This study is expected to provide theoretical contributions in the development of legal science related to the protection of victims of domestic violence and practical benefits for the community, law enforcement officers, and related institutions to increase the effectiveness of law enforcement. These findings also emphasize the importance of a holistic approach in handling cases of domestic violence, involving community education, victim empowerment, and system strengthening. Keywords: criminal act, domestic violence, Law Number 23 of 2004 ABSTRAK Penelitian ini bertujuan untuk menganalisis perlindungan hukum terhadap korban tindak pidana kekerasan dalam rumah tangga (KDRT) di Kota Binjai berdasarkan Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga. Penelitian ini didasarkan pada meningkatnya kasus KDRT di Indonesia, yang mengindikasikan masih adanya kendala dalam implementasi Undang-Undang Nomor 23 Tahun 2004. Fokus penelitian meliputi penegakan hukum terkait KDRT dan hambatan yang dihadapi di dalamnya. Penelitian ini menggunakan metode deskriptif dengan pendekatan hukum normatif, yang mengacu pada peraturan analisis peraturan-undangan, teori hukum, dan dokumen pendukung lainnya. Data sekunder diperoleh dari literatur seperti buku, jurnal, dan hasil penelitian sebelumnya. Penelitian ini diharapkan dapat memberikan kontribusi teoritis dalam pengembangan ilmu hukum terkait perlindungan korban KDRT dan manfaat praktis bagi masyarakat, aparat penegak hukum, serta lembaga terkait untuk meningkatkan efektivitas penegakan hukum. Temuan ini juga menekankan pentingnya pendekatan holistik dalam penanganan kasus KDRT, melibatkan edukasi masyarakat, pemberdayaan korban, dan penguatan sistem. Kata Kunci : Hukum Pidana, Kekerasan Dalam Rumah Tangga, Undang-Undang Nomor. 23 Tahun 2004